Parentinguistic: Parenting Supportive Message of Expressive Act in Parenting Perspective - Kurniawan, Kurniawan (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2023)
This research focuses on the use of parental support messages for children and what these messages mean. Messages of support are a form of positive communication to encourage children to become better individuals. This research used the qualitative method. In answering the formulation problem, speech act theory was used by Yule (2006) which was elaborated by Duncan (2009) regarding messages of support, and Wolfson & Judd (1983) about the meaning behind these support messages. The data in this study are expressive utterances that contain praise, approval, and encouragement originating from films about parenting. The data were collected using listening and note-taking techniques and then analyzed using Spradley (2016). From the research that has been done, it is concluded that each message of support conveyed has its own aims and objectives. The delivery of messages of support is influenced by the background of speakers and speech partners. Those indicate that parenting support messages play a role in parent-child communication. Its main role is to strengthen solidarity and maintain harmony between speakers. So, the language aspect must be considered by parents. This research used term â€œParentinguisticâ€ or abbreviation of Parenting Linguistic, to invite further research on the relationship between parenting and language.